Crise, resistência e luta dos trabalhadores em educação do Ceará, libertar o sindicato ou libertar-se do sindicato: o caso do SINDIUTE. - Paula, Maria Valdecir Abreu de (2010)
The current study argues on the Education workers’ trade union organization in Ceará, which originated the Education Workers Union (SINDIUTE). Its primary aim is registering the historical struggle of such entity as an instrument of workers’ resistance from the 1980’s. The research intends to recall organization’s main efforts and achievements against the offensive of the varied governments, the crisis that the institution faced by 1991, the rupture of Union workers’ sector (Union articulation) that came into light by the end of the 1990’s, and the abandon of the Union by its managers, in 2003. For such, it seeks to criticize the politics and the organization that the worker class lived in the 1990’s, facing the world economic crisis. The study denounces legal procedures Brazilian last governments adopted from that decade and analyzing the feedback of worker class, particularly the united one, in a national plan, within CUT, and in a state plan, within SINDIUTE. The study shows to be contrary to the proposition/defense character that CUT’s main sector performed since that. It denounces attacks to union workers’ freedom and autonomy that marked SINDIUTE’s foundation based on actions of government and sectors of the very category. Therefore, the research refuses the idea of work centrality loss within contemporary world, position that the sector that denied SINDIUTE in 2003, Radical Critics, assumed, defending union workers’ efforts abandon. Analysis here confirms the evaluation that workers union movement lives a critical period, due to both, the increasing of working power, and the crisis of managers, configured with the position of defense/proposition that the main Brazilian trade sector adopted. Nonetheless, it reaffirms the essential trade unions role in the context of the general fight for the emancipation of workers class, which stipulates its immediate task of recomposing the independence of class and the autonomy of their trade unions facing pseudo-democratic and popular governments, as well as bosses. It defends as a primary need let the workers union free from the defensive politics of most of managers, from its increasing capture by trade union’s structure and economic imperatives.